2019
DOI: 10.1002/aur.2209
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processes predicting advanced theory of mind in the broader autism phenotype

Abstract: Little is known about executive functions (EFs) associated with advanced theory of mind (ToM) abilities. We aimed to determine if advanced ToM abilities were reduced in individuals with subclinical traits of autism spectrum disorder (ASD), known as the “Broader Autism Phenotype” (BAP), and identify the EFs that predicted unimpaired performance on an advanced ToM task, the faux pas test. We assessed 29 participants (13 males) with the BAP who were relatives of children with ASD. Thirteen participants showed red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 113 publications
2
10
0
1
Order By: Relevance
“…The broader autism phenotype (BAP) was proposed to indicate a collection of sub-clinical expressions of autistic traits 46 50 . The BAP is qualitatively similar to autism, but neither leads to the full autism phenotype nor results in significant difficulties in socio-cognitive functioning 46 , 47 . Studies have observed that BAP is especially prevalent in the relatives of autistic people, for example, 20–40% of first-degree relatives but 2–9% of the general population 47 , indicating that autism is highly heritable 51 53 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The broader autism phenotype (BAP) was proposed to indicate a collection of sub-clinical expressions of autistic traits 46 50 . The BAP is qualitatively similar to autism, but neither leads to the full autism phenotype nor results in significant difficulties in socio-cognitive functioning 46 , 47 . Studies have observed that BAP is especially prevalent in the relatives of autistic people, for example, 20–40% of first-degree relatives but 2–9% of the general population 47 , indicating that autism is highly heritable 51 53 .…”
Section: Introductionmentioning
confidence: 99%
“…The BAP is qualitatively similar to autism, but neither leads to the full autism phenotype nor results in significant difficulties in socio-cognitive functioning 46 , 47 . Studies have observed that BAP is especially prevalent in the relatives of autistic people, for example, 20–40% of first-degree relatives but 2–9% of the general population 47 , indicating that autism is highly heritable 51 53 . Parents of autistic children (BAP) are about three times more likely to have autistic traits than parents of non-autistic children (non-BAP), especially in the communication and social skills domains 54 56 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The psychological and cognitive processes that support ToM remain a matter of debate (Brewer et al, 2017; Rosenthal et al, 2019). Facial and vocal emotion processing, mental state reasoning, and various executive functions such as attention switching, working memory and cognitive flexibility, among others, are all believed to contribute to ToM processing (Brewer et al, 2017; Green et al, 2020), and probably reflect a multilevel structure that involves both cognitive and affective processes and the interactions between them (Schurz et al, 2021). This translates into multiple instruments having been developed to measure ToM, or specific aspects of ToM, including false belief, mental state attribution, and various formats of attribution of intentions (AI) (Brewer et al, 2017; Livingston et al, 2019).…”
Section: Introductionmentioning
confidence: 99%